PENGARUH PERBANDINGAN TERIGU DENGAN TEPUNG KECAMBAH KACANG GUDE (Cajanus cajan (L.) Millsp.) TERHADAP KARAKTERISTIK ROTI TAWAR - Sayang Putra, Dewa Gede; Wisanyasa, Ni Wayan; Trisna Darmayanti, Luh Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 4 No 1 (2015): Jurnal ITEPA, 2015)
This study aims to determine the effect of wheat flour and sprout pigeonpea flour on the characteristic of white bread and to find out the best ratio of wheat flour and sprout pigeonpea flour to produce white bread with the best characteristic. The design of research was Completely Random Design (CRD). The treatment factor was ratio of wheat flour and sprout pigeonpea flour with 5 level: 100%:0%, 95%:5%, 90%:10%, 85%:15% and 80%:20%. Each treatment was repeated three times in order to obtain 15 experimental units. The results showed that the ratio of wheat and sprouts pigeon pea flour in the production of white bread has siginificant effect on the moisture content, ash content, protein content, crude fiber, bread improver, color, texture, flavor, taste, pores uniformity and overall acceptability. The best characteristic of white bread was indicated by application of ratio wheat flour and sprout pigeon pea flour is 85%:15%. The characteristic were 29.58% for moisture content, 1.54% for ash content, 10.44% for protein content, 9.04% for crude fiber, 384.55% for bread volume, color was liked, slightly soft texture, flavor was liked, taste was liked, pores uniformity of bread was mostly uniform and liked the overall acceptance.
Keywords: wheat flour, sprouts pigeonpea flour, white bread